A Customer Relationship Management Roadmap for a Healthcare Service Company - Chauhan, Trishala; Sindhu, Shilpa (Indian Journal of Computer Science, 2024)
The present paper seeks to analyze the Customer Relationship Management (CRM) of a Healthcare service company (Pseudonym) operating in a particular locality. The company provides an online platform to avail of prescribed & OTC Products as well as diet and fitness supplements, baby & mother care products, herbal products & surgical supplies. CRM is a technical process that is used by business houses and other organizations to maintain a continued relationship with their customers. Big data or large information becomes the basis of CRM. The main purpose of this paper is to analyze all the CRM tools used by the healthcare service company and to propose a best customer service/sales profile for the company. A framework for CRM is prepared by analyzing all the CRM tools used by the company. The Customer Service/Sales profiles are divided into three categories, that is, pyramid, hourglass, and hexagon. All profiles are made of interrelations between three service levels i.e., initial transactions, repeat customers, and customer advocates. It is substantiated that the Hexagon customer service/sales profile suits the business of the company. The findings of this paper will help the healthcare service companies to strengthen RM strategies. The proposed framework of social CRM will help the healthcare companies to streamline their communication strategies. This framework is like a checklist of social CRM tools. Various social CRM tools are available in the market. The companies can create continuous channels of interaction for their products/services.